ON INTEGRAL OPERATORS WITH FIBER SINGULAR TYPE HOMOGENEOUS KERNELS IN THE SPACE LP(R2). - V.М. DEUNDYAK; H.A. STEPANUCHENKO (Advanced Engineering Research)
A new class of integral operators with fiber singular type homogeneous kernels in the space Lp(R2) is introduced. This new class includes the class of operators with SO(2)-invariant homogeneous kernels. For Banach algebra of pair operators with fiber singular type homogeneous kernels the symbol calculus is constructed and the criterion of Fredholmness is obtained.